Land Cover Mapping and Prediction Using Cellular Automata and Markov Chain (Case Study: Depok City, Indonesia) - Muhammad Arya Pradipta; Megivareza Putri Hanansyah; Filsa Bioresita; Noorlaila Hayati; Lalu Muhamad Jaelani; Bangun Muljo Sukojo, Husnul Hidayat (Geoid, 2026)
Depok City, a satellite city of Jakarta, is experiencing massive urbanization due to Jakarta's role as an economic hub, leading to significant land-use changes. This study analyses land cover in Depok City annually from 2017 to 2024 across five categories: Built-up Area, Vegetation, Agricultural Land, Bare Land, and Water Body. This process utilizes the Extreme Gradient Boosting algorithm applied to Sentinel-2 Level-1C satellite imagery for the specified period. Subsequently, we predict Depok City's land cover conditions for the year 2042 using a Cellular Automata-Markov Chain simulation. This simulation incorporates historical land cover maps, which were generated previously, along with driving factors such as distance from main roads and distance from health and educational facilities. The year 2042 was chosen to coincide with the expiration of Peraturan Daerah Nomor 9 Tahun 2022, law product concerning the Depok City Spatial Plan for 2022-2042. The final outputs of this research are land cover maps of Depok City for each year from 2017 to 2024, as well as a predicted land cover map for Depok City in 2042. The study found that from 2017 to 2024, the built-up area and vegetation land cover category showed an increasing trend in extent, while the remaining land cover categories decreased. Prediction model of year 2042 shows predicted expansion of Built-Up land and Vegetation land cover categories, while other land cover categories predicted to decrease.